Perbandingan Persepsi dan Kemandirian Belajar Matematika Siswa Madrasah Terhadap Pembelajaran Daring Ditinjau Dari Kemampuan Awal Matematis - Agus Supardi; Hepsi Nindiasari; Syamsuri Syamsuri (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
This research is motivated by the continuing development of the Covid-19 pandemic, which has changed the teaching and learning environment in schools, which was initially face-to-face or conventional. Now, it must be carried out online or online to break the chain of spreading the virus. In the study, three groups of students will be compared based on Mathematical Initial Ability (KAM), namely: high KAM, medium KAM, and low KAM. The research method used in this research is comparative research. Comparative research is directed to determine whether there are differences between two or more groups in the aspects or variables studied. In this study, the variables studied were the perception of learning and students' learning independence in online learning. The goal is to see the perception and independence of learning in online learning using google classroom. So that it can be seen the relationship between the independent variable and the dependent variable, in this study, the independent variable is online learning (X), and the dependent variable is student perception (Y1) and student learning independence (Y2). So it can be concluded that the perceptions of class VIII students of MTsN 1 Cilegon City about online learning if viewed from high, medium, and low initial mathematical abilities, there is no difference, while for student learning independence based on the one-way ANOVA test it is known that the significance value is 0.758 or H0 is rejected. . Because the significance value is more significant than 0.05, namely 0.758> 0.05, it can be concluded that there are differences in students' learning independence in online learning in terms of high, medium and low initial mathematical abilities.